2020
DOI: 10.35940/ijeat.c5775.029320
|View full text |Cite
|
Sign up to set email alerts
|

ML Methods for Crop Yield Prediction and Estimation: An Exploration

Abstract: Machine learning Has performed a essential position within the estimation of crop yield for both farmers and consumers of the products. Machine learning techniques learn from data set related to the environment on which the estimations and estimation are to be made and the outcome of the learning process are used by farmers for corrective measures for yield optimization. This paper we explore various ML techniques utilized in crop yield estimation and provide the detailed analysis of accuracy of the techniques. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…of pest spry, no. of weeds spry, and eight binary categorical (0 for absence and 1 for presence) agronomical features, i.e., seed treatment, soil-type chikny loom, varieties adoption, harvest period April (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), planting in November, land irrigated, farmers' area >25 acres, and seed type, is used in the current study. Experiment is performed using Python's key library called scikit-learn (Sklearn) by Jupyter Notebook as https://scikitlearn.org/stable/supervised_learning.html.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…of pest spry, no. of weeds spry, and eight binary categorical (0 for absence and 1 for presence) agronomical features, i.e., seed treatment, soil-type chikny loom, varieties adoption, harvest period April (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), planting in November, land irrigated, farmers' area >25 acres, and seed type, is used in the current study. Experiment is performed using Python's key library called scikit-learn (Sklearn) by Jupyter Notebook as https://scikitlearn.org/stable/supervised_learning.html.…”
Section: Methodsmentioning
confidence: 99%
“…Machine learning is viewed as innovative extension of statistics capable of dealing with the massive datasets by adding the methods from computer science to the repertoire of statistics [19]. Machine learning is categorized as advanced tools applied for the prediction of agricultural production [20][21][22][23]. According to Jeong et al [9], machine learning used latest process-based techniques as an alternative to traditional statistical modeling.…”
Section: Supervised Machine Learningmentioning
confidence: 99%
“…Using the data analytics tool R, the trials were run on soil data made up of 110 sample samples [19]. The experimental results showed that the JRIP algorithm performed better because it had advanced delicacy and a roughly 1.0 kappa statistic [20].…”
Section: Literature Surveymentioning
confidence: 99%
“…The optimization of machine learning algorithms has become a significant part for model deployment and got abundant attention of researchers being a core components of optimized machine learning algorithms for the massive amount of data (Sun et al, 2019). Machine learning (ML) algorithms has been categories as an advanced tool, being used for the prediction of agriculture production (Alagurajan and Vijayakumaran, 2020;Gonzalez Sanchez et al, 2014;Yadav et al, 2020). An optimized crop model is foremost need of the time is to handle the food trepidations (Elavarasan and Vincent, 2021a;Jeong et al, 2016).…”
Section: Research Articlementioning
confidence: 99%